Political Dynasty in Banten: Improvement or Threat to Democracy - Indrawan, Jerry; Simanihuruk, Hermina; Aji, M. Prakoso (Administratio, 2020)
In many developing countries, namely in South East Asia, political leaderships are marked by numerous hereditary systems, also include Indonesia. Banten is the writers selected region as a research subject in this writing. The former Governor of Banten, Ratu Atut Chosiyah, has relatives in seven regencies and cities all across Banten, including national scale, in such creates her own political dynasty. This paper are about to answer two questions and reveal some close facts to discuss in Indonesia related to political dynasty. Does this hereditary systems works well in serving the people’s need? Does political dynasty close other people opportunity to run for public offices as well? If this so, political dynasty will be a threat for ongoing Indonesian democratic practices, especially bureaucratic reform efforts. Research metdhod is done through qualitative descriptive with literature study to gain data and information required. The conclusion of this writing is that political dynasty do more harm than give benefit and it would definitely endanger the lives of local democracy. In terms of public service, little advantages received from this sort of practices.